Effect of Pd doping in (Fe/Ni)/CeO2 catalyst for the reaction path in CO2 oxidative ethane dehydrogenation/reforming. (1st November 2021) - Li, Xiuquan; Yang, Zhongqing; Zhang, Li; He, Ziqiang; Fang, Ruiming; Wang, Ziqi; Yan, Yunfei; Ran, Jingyu
Abstract: The catalytic reaction of C2 H6 with CO2 provides an opportunity to use shale gas and the greenhouse gas as source materials to produce ethylene through oxidative dehydrogenation or produce syngas through dry reforming. In this work, the reaction characteristics of ethane with CO2 on Fe/Co/Ni/Cu monometallic catalysts and Pd-doped bimetallic catalysts were studied through activity test, kinetic analysis, catalyst characterization and DFT calculation. It is found that Pd–Fe6 /CeO2 has a high and stable C2 H4 selectivity of 80.4%, which is suitable for oxidative dehydrogenation reaction, while Ni6 /CeO2 has a large ethane/CO2 conversion and a high CO selectivity of 96.5%, which is suitable for dry reforming reaction. For Fe-based catalyst, the doping of Pd form double active component structure. It only reduces the energy barrier of ethylene formation and CO2 direct activation to provide O∗, but also increases the energy barrier of ethylene deep dehydrogenation, thus increasing the conversion of reactants and selectivity of C2 H4 . For Ni-based catalysts, the doping of Pd forms the alloy structure, which reduces the energy barrier of O∗-assisted dehydrogenation reaction and increases the conversion of reactants, but increases the energy barrier of C–C bond cleavage and CO2 activation reaction, which reduces the selectivity of reforming to syngas. Graphical abstract: Image 1 Highlights: Taking into account the value-added conversion of C2 H6 and the utilization of CO2 . The selectivity of ethylene on the Pd–Fe6 /CeO2 catalyst is over 80%. Pd doping increases energy barrier of CO2 -assisted dry reforming for Ni catalyst. Doping of Pd forms double active structure with Fe and alloy structure with Ni.